Epidemiology of Kawasaki Disease in children in Switzerland: a national prospective cohort study (Swiss Medical Weekly, 2022)
AIM OF THE STUDY: Kawasaki disease is a febrile illness which can lead to significant coronary artery lesions. Its incidence varies among countries and is highest in Japan (330.2 children under 5 years old/100,000 per year). Since the epidemiology of Kawasaki disease in Switzerland is unknown, we conducted a national prospective data collection between 2013 and 2017 to describe its incidence, diagnosis, and treatment.METHODS: We collected demographic and clinical data of the children under 17 years old hospitalised with Kawasaki disease in Switzerland between March 2013 and February 2017 using anonymous data collection forms with the help of the Swiss Paediatric Surveillance Unit (SPSU). We defined Kawasaki disease per the 2004 American Heart Association criteria: patients with ≥5 days of fever and ≥4 of the 5 main clinical features were included as complete Kawasaki disease and patients with ≥5 days of fever and